NOTES ON ECONOMIC DEVELOPMENT IN A DUAL ECONOMY: THE RISE AND FALL OF BRAZILIAN MANUFACTURING INDUSTRY - Feijo, Carmem Aparecida do Valle Costa; Lamonica, Marcos Tostes (Práticas de Administração Pública, 2022)
Since the second half of 2010, the Brazilian economy is stagnant with negative consequences on productivity and employment growth. We will argue that the loss in economic dynamism is rooted in significant structural changes since the economic opening in the 1990s, resulting in fast deindustrialization and deterioration in the labour market. Our theoretical hypothesis is that of endogenous technical progress. Assuming that it is incorporated in the new machines and equipment, capital accumulation is the key variable to explain. Following early works by Kaldor and Kaldor Mirrlees, we assume that capital accumulation and the incorporation of technical progress are fundamental to promoting structural transformation. However, the presence of a dual labour market may impair the process. Also, as explained by the new developmentalist theory, financial integration of developing economies (a strategy to grow with external savings) in a hierarchial international monetary-financial system imply that real interest rates tend to be high, and the real exchange rate is appreciated, which does not induce accumulation in productive capital. In this case, the economy tends to specialize in its comparative advantages. Early deindustrialization deepens economic heterogeneity and operates as a barrier to increasing aggregate productivity. This is the case of Brazilian economy that failed to develop an endogenous core of technical progress during the fast industrialization process and did not succeed after economic opening either. Duality in the labour market and productivity heterogeneity have been deepened since the 1990s and the Brazilian economy is stagnant